Teaching practical numeracy through social justice pedagogy : case study of Abu Dhabi Women's College - Tanko, Mohammed Goma (Curtin University, 2012)
The study presented in this thesis investigates the impact of using Social Justice Pedagogy in teaching Practical Numeracy to Diploma Foundation Students, in Abu Dhabi Women’s College (ADWC), of the Higher Colleges of Technology, in the United Arab Emirates (UAE). Gutstein’s (Gutstein, 2003, 2006a, 2007) framework for teaching mathematics for Social Justice was utilised. His framework had both social justice goals and mathematics goals. Productive Pedagogical principle (Mills, et al., 2009) was utilised as a framework to reflect on teaching practices in this study.In order to achieve credibility and validity in data collection and interpretation of results, triangulation method was utilised in accordance with (Cooper 2001), and grounded theory for analysis, in accordance with Strauss and Corbin (1998), and Charmaz (2008).There were twenty participants in this research. Their ages ranged from sixteen top thirty-six years and all of them were among the body of students whom I taught (class DF203). Three students’ projects were completed in this research work, namely Time of Travel (TT), Career Aspirations (CA) and Car Parking (CP). The topics were chosen based on individual participant’s interest after brain-storming sessions in my class and all dealt with one or more issues that have social justice implications. The TT project group investigated ways in which the transport, provided by the college, could be improved – they utilised mathematics as a tool to understand the challenges they face and made recommendations to the college Transport Coordinator on how to change and / or improve this very important aspect of their college life. The action taken by the TT project group contributed to a change in college start times from 7:30 am to 8:30 am for the students at Abu Dhabi Women’s College (ADWC).The CP project group thought the parking allocation at ADWC was unfair (teachers have more space per head than students). Therefore, they used mathematics as a tool to investigate the car parking space allocation at ADWC. It was also as a result of the actions taken by the CP project group that students’ car parking space was significantly increased at ADWC. The CA project group used mathematics as a tool to investigate and inform the College Career Coordinator on how informed, or otherwise, the students in the Diploma Foundations (DF) at ADWC were, with regard to the career opportunities available to them. Similarly, as a result of the action taken by the CA group, Career Fairs at ADWC now feature information on part-time jobs and not only on full-time jobs as was the case before this project.For my students the Social Justice Pedagogy employed within their classroom gave them unprecedented insight into their learning processes. For the first time they took responsibility for learning outcomes rather than have them dictated by their teacher mentor or, equally common, their reference to the answer section at the back of a text book! By applying mathematics to their everyday lives it suddenly became relevant to them and they realised the potential which it could have for changing often long-established norms. Equally, it was both interesting and salutary for me, the researcher, to be made aware, through frequent discussion with the students, just how limiting the social and cultural constraints are within the society of which the students are a part (McIntosh, 14th November, 1990). It is reasonable to assert that, limited in scope though the research has been; it has, nonetheless, supported the assertions of those who had hitherto engaged in the same field and it has also added to the limited literature available on the teaching of Mathematics for Social Justice.